2018
DOI: 10.13005/bpj/1358
|View full text |Cite
|
Sign up to set email alerts
|

Erythema Multiforme: A Recent Update

Abstract: Erythema multiforme (EM) is an acute, self-healing inflammatory mucocutaneous disorder which presents with diverse spectrum of cutaneous lesions, hence termed “multiforme”. Oral lesions are quite characteristic and manifest as rapidly rupturing vesicles & bullae forming ill-defined erosions and hemorrhagic encrusted lip lesions. Wide variety of triggering factors for EM have been documented in the literature, but history of prior herpes simplex virus (HS) infection is most widely accepted. Most other case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 20 publications
1
18
0
2
Order By: Relevance
“…The exact aetiology of EM is obscure, although, prior infection with herpes simplex virus (HSV) and the intake of certain drugs are the common precipitating factors. 9,10 Our findings demonstrated that 63.3% of the patients with ORF were less than 40 years of age and these findings are consistent with the report of the Center for Disease Control and Prevention (CDC) that found that the majority of ORF cases were reported within the third or fourth decade of age. 11 The results of our study also revealed that the sites of infection were distributed as follows: right hand in 8 patients (26.7%), left hand in 19 patients (63.3%), and right and left hands in 3 patients (10%).…”
Section: Discussionsupporting
confidence: 90%
“…The exact aetiology of EM is obscure, although, prior infection with herpes simplex virus (HSV) and the intake of certain drugs are the common precipitating factors. 9,10 Our findings demonstrated that 63.3% of the patients with ORF were less than 40 years of age and these findings are consistent with the report of the Center for Disease Control and Prevention (CDC) that found that the majority of ORF cases were reported within the third or fourth decade of age. 11 The results of our study also revealed that the sites of infection were distributed as follows: right hand in 8 patients (26.7%), left hand in 19 patients (63.3%), and right and left hands in 3 patients (10%).…”
Section: Discussionsupporting
confidence: 90%
“…16,17 Erythema multiforme (EM) is an acute self-limiting, immunological, vesiculobullous disorder primarily affecting the skin and mucous membrane. 18 Based on the area of involvement it was classified as major and minor. Minor EM involves only the cutaneous region as seen in our study, whereas EM major involves both the mucous membrane and also the cutaneous regions.…”
Section: Discussionmentioning
confidence: 99%
“…Erythema multiforme (EM) is a rare immune-mediated mucocutaneous disorder with acute onset, sometimes recurrent, and sometimes self-limited. 1 , 2 The two main forms of EM are EM major with the involvement of two or more mucosal sites and EM minor with the involvement of one or none mucosal site. 3 The etiology of EM remains unknown, but infections, certain drugs, immune conditions, and malignancies can trigger the development of this condition.…”
Section: Introductionmentioning
confidence: 99%
“… 3 The etiology of EM remains unknown, but infections, certain drugs, immune conditions, and malignancies can trigger the development of this condition. 2 , 4 Frequent episodes occurring over several years characterized recurrent erythema multiforme (REM). 5 Approximately 70% of REM cases are caused by the herpes simplex virus (HSV).…”
Section: Introductionmentioning
confidence: 99%